Return on investment of a model of access combining triage with initial management: an economic analysis. Issue 7 (21st July 2021) - Snowdon, David A; Harding, Katherine E; Taylor, Nicholas F; Leggat, Sandra G; Kent, Bridie; Lewis, Annie K; Watts, Jennifer J
Abstract : Objectives: Timely access to outpatient services is a major issue for public health systems. To address this issue, we aimed to establish the return on investment to the health system of the implementation of an alternative model for access and triage (Specific Timely Appointments for Triage: STAT) compared with a traditional waitlist model. Design: Using a prospective pre–post design, an economic analysis was completed comparing the health system costs for participants who were referred for community outpatient services post-implementation of STAT with a traditional waitlist comparison group. Setting: Eight community outpatient services of a health network in Melbourne, Australia. Participants: Adults and children referred to community outpatient services. Interventions: STAT combined targeted activities to reduce the existing waiting list and direct booking of patients into protected assessment appointments. STAT was compared with usual care, in which new patients were placed on a waiting list and offered appointments as space became available. Outcomes: Health system costs included STAT implementation costs, outpatient health service use, emergency department presentations and hospital admissions 3 months before and after initial outpatient appointment. Waiting time was the primary outcome. Incremental cost-effectiveness ratios (ICERs) were estimated from the health system perspective. Results: Data from 557 participants showed a 16.9 days or 29% (p<0.001) reduction in waiting time for first appointment with STAT compared with traditional waitlist. The ICER showed a cost of $A10 (95% CI −19 to 39) per day reduction in waiting time with STAT compared with traditional waitlist. Modelling showed the cost reduced to $A4 (95% CI −25 to 32) per day of reduction in waiting, if reduction in waiting times is sustained for 12 months. Conclusions: There was a significant reduction in waiting time with the introduction of STAT at minimal cost to the health system. Trial registration number: Australian New Zealand Clinical Trials Registry (ACTRN12615001016527).